Is Ultrasound Fusion a Reasonable Replacement for Computed Tomography in Guiding Abdominal Interventions?. (18th April 2016) - Ahmed, Yasmine; Novak, Ronald D.; Nakamoto, Dean; Azar, Nami
Abstract : Objectives: To compare the diagnostic yield, complication rate, and procedure length of ultrasound fusion‐guided liver biopsy to the diagnostic yield, complication rate, and procedure length of computed tomography (CT)‐guided liver biopsy; to measure the average ionizing radiation dose that patients are exposed to during a typical CT‐guided liver biopsy procedure; and to present relevant and interesting cases of ultrasound fusion‐guided abdominal interventions to describe the efficacious use of the technology. Methods: A retrospective analysis of 63 patients who had image‐guided liver biopsies performed at our institution was completed. Patient records were divided into 2 groups according to the type of image guidance used during the procedure (ultrasound fusion versus CT), and data were compared by the χ 2 test, Student t test, and Mann‐Whitney U test. Results: The diagnostic yields and complication rates were not statistically significantly different between the modalities. The average procedure durations were significantly different: ultrasound fusion‐guided biopsy, 31.63 minutes; compared to CT‐guided biopsy, 61.67 minutes ( P = .003). Conclusions: Diagnostic yields and complication rates were comparable for ultrasound fusion and CT. However, the average procedure duration for an ultrasound fusion‐guided liver biopsy was approximately half that of CT‐guided liver biopsy, likely increasing both cost‐effectiveness and patient satisfaction.